Potentiation of ryanodine receptor–mediated calcium release by MAPK is responsible for epidermal transformation and carcinogenesis - Pengcheng Wang; Kristan H. Cleveland; Ayaz Shahid; Chathurika Rathnayaka; Farideh Amirrad; Zhenpeng Song; John Paul Estillore; Ruiwu Wang; Thomas G. Back; S. R. Wayne Chen; Ying Huang (Proceedings of the National Academy of Sciences, 2025)
Epidermal growth factor (EGF) induces anchorage-independent growth in promotion-sensitive (P + ) mouse epidermal cell model JB6 primarily through activation of the MAPK/ERK signaling pathway. The β-blocker carvedilol inhibits EGF-promoted JB6 transformation, but the underlying mechanism is unknown. Since carvedilol suppresses overactivated ryanodine receptors (RyRs) independently of its adrenergic blocking effects, we hypothesized that EGF-promoted transformation requires RyR-mediated calcium (Ca 2+ ) release and that carvedilol inhibits transformation via targeting RyRs. All RyR subtypes were present in epidermis and strongly upregulated by ultraviolet (UV) radiation, as demonstrated in an RyR2-tdTomato reporter mouse model. In vitro, EGF induced ERK phosphorylation and RyR2 upregulation and increased RyR agonist 4-chloro-m-cresol (4-CMC)-evoked Ca 2+ release, which is inhibitable by structurally divergent RyR stabilizers and inhibitors of MAPK and PLC, but not by most β-blockers. Expression of constitutively active K-RAS and MEK-1 or UV also potentiated 4-CMC-evoked Ca 2+ release. RyR agonists and the Ca 2+ ionophore ionomycin promoted JB6 transformation while RyR stabilizers, the intracellular Ca 2+ chelator BAPTA/AM, and inhibitors of MAPK and PLC blocked transformation. The RyR shRNAs abolished the transformation-inhibitory effect of carvedilol. The IC 50 values of five carvedilol derivatives for suppressing RyR-mediated Ca 2+ release positively correlated with the IC 50 values for transformation inhibition. In vivo, UV-induced DNA damage and skin inflammation were enhanced by topical 4-CMC treatment but attenuated in the RyR2-E4872Q knock-in mice in which RyR2 activity is reduced. Human skin tissue microarray analysis confirmed spatial colocalization of phospho-ERK and RyR2 in the same tumor areas. Thus, potentiation of RyR-mediated Ca 2+ release by MAPK is an important pathway leading to carcinogenesis.